Modelling of integrated local energy systems: Low-carbon energy supply strategies for the Oxford-Cambridge arc region. (October 2021) - Chaudry, Modassar; Jayasuriya, Lahiru; Jenkins, Nick
Abstract: The energy supply system is undergoing enormous change to deliver against cost, security of supply and decarbonisation objectives. Robust decisions on the provision of infrastructure requires integrated models to perform analytics across the entire energy supply chain. A national level combined gas and electricity transmission network model was upgraded to represent local energy systems. Multiple energy vectors including electricity, gas, hydrogen and heat were integrated within the modelling framework. The model was utilised for a study of the Oxford-Cambridge arc region. The study assessed how different energy supply strategies, from electrification of heat to use of 'green' gases or local heat networks, could affordably reduce carbon emissions from the Oxford-Cambridge arc region energy system whilst considering constraints from the national system. The modelling process generated a diverse range of options for energy supplies, the choice of supply networks and end use technologies. The analysis illustrated the cost effectiveness and emission reduction potential of electrification of heat despite the requirement for additional network and supply capacity. Additionally, insulation and other energy efficiency solutions were also analysed. Potential barriers to technological change such as upfront costs, lack of awareness and perceived technology shortcomings were discussed in the context of the strategies assessed. Highlights: An integrated national and local energy systems modelling approach is described. Four contrasting regional energy supply strategies in GB are investigated and compared. The use of low-carbon electricity for heating was found to cost-effectively reduce emissions. A heat networks strategy increases distributed energy supply but incurs high capital costs. The use of hydrogen remains prohibitive despite the potential to reduce emissions.